2010
DOI: 10.1111/j.1365-2036.2010.04371.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: antioxidant supplements for liver diseases – the Cochrane Hepato‐Biliary Group

Abstract: SUMMARY BackgroundSeveral liver diseases have been associated with oxidative stress. Accordingly, antioxidants have been suggested as potential therapeutics for various liver diseases. The evidence supporting these suggestions is equivocal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…For many years, much money has been spent, but no great achievement has been made in the field of antioxidant therapy for hepatitis B. A meta-analysis conducted in 2010 concluded that there was no evidence to support or refute antioxidant therapy in liver diseases (114) despite the fact that oxidative stress plays a major role in the pathogenesis of hepatitis B. Therefore, the time is right to canalize our research in a standardized direction.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, much money has been spent, but no great achievement has been made in the field of antioxidant therapy for hepatitis B. A meta-analysis conducted in 2010 concluded that there was no evidence to support or refute antioxidant therapy in liver diseases (114) despite the fact that oxidative stress plays a major role in the pathogenesis of hepatitis B. Therefore, the time is right to canalize our research in a standardized direction.…”
Section: Discussionmentioning
confidence: 99%
“…The most attention was paid to digestive system disorders: stomach and intestine cancer [93][94][95][96], colorectal adenoma [97], various other gastrointestinal disorders [98,99], and liver diseases [100]. However, the range of works included also other types of diseases: cardiovascular, nervous, osteoarticular, renal, endocrine, ocular, dermal, and nonorgan-specific [98,99].…”
Section: Meta-analysis Of Results Of Studies On the Effectiveness Of mentioning
confidence: 99%
“…Despite these limitations, it can be summarized that (1) the use of vitamin E is associated with a decrease in aminotransferases in subjects with NASH, (2) studies where histologic endpoints were evaluated indicate that vitamin E causes improvement in steatosis, inflammation, and ballooning and resolution of steatohepatitis in adults with NASH, and (3) vitamin E has no effect on hepatic fibrosis. Although two meta-analyses 8,129 failed to observe significant histological benefits with vitamin E in patients with NASH, these analyses were conducted before PIVENS 122 and TONIC 130 trials were published. In the largest clinical trial (PIVENS) 122 reported to date, the pure form of rrr a-tocopherol was orally administered at a dose of 800 IU/day for 96 weeks.…”
Section: Vitamin Ementioning
confidence: 99%